Validity of marti's thought in the cuban revolutionary sport philosophy - María de Lourdes Rodríguez-Pérez; Laura Elena Roberto-Rodríguez; Pedro Aciel Díaz-Rodríguez (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2013)
On José Martí long pilgrimage around the world, nothing was estranging for him. Nobody as he knew how to describe with so much beauty, emotion and analytic Revista electrónica de Ciencia y Tecnología en la Cultura Física vision the facts and the environment that surrounded him. In the informative journalistic branch he covered, among other things, reports with sport traits. It is highlighted the correct relationship that he found between the physical exercise and the mental health offering in his chronicles an appropriate valuation of the Physical Culture social necessity. Martí was ahead to the campaign that today it is carried out against the sedentary lifestyle and the physical inactivity when he praised the importance of the exercise in the man's life. His experience together with the journalistic profession that he exercised during long years, qualified him to emit concepts regarding to the scientific content of the physical culture, not exempt of aesthetic and humane valuation, studying the man like a biological, psychological and social entity, thought that maintains today a full validity. The aspects related with the sport and the physical education previously referred are analyzed and examined in the work through textual appointments of the chronicles written by the apostle, which have connections with some Fidel Castro's statements expressed on his speeches about the importance of the sport and it characteristics in the revolutionary stage in which its reflected the validity o The Teacher's ideas.